Optimization Model of Media Selection through Integer Programming - Safiza Salleh; Siti Haida Ismail; Haslaile Abdullah (International Journal of Applied Business and Information Systems, 2020)
The impact of communication through advertisement and promotion plays a vital role in the success or failure of products and services. Media planning is required for selection of advertising media and development and allocation of the advertising resources. Therefore, the aim of this paper is to develop an integer programming on media selection for maximizing audience exposure in promoting Technical Education and Vocational Training (TVET) skill training offer in Malaysia particularly for the school leavers. This paper addresses the problem for media selection that can maximize audience exposures considering a list of constraints ranging from costing per media, days for preparation and operational expenditure. The model was designed based on the integer programming method and the solution obtained shows the decision aids in selecting an effective media mix in order to achieve maximum performance in promoting skills training programs.